2003
DOI: 10.1242/jcs.00726
|View full text |Cite
|
Sign up to set email alerts
|

Shear flow-induced motility ofDictyostelium discoideumcells on solid substrate

Abstract: Application of a mild hydrodynamic shear stress to Dicytostelium discoideum cells, unable to detach cells passively from the substrate, triggers a cellular response consisting of steady membrane peeling at the rear edge of the cell and periodic cell contact extensions at its front edge. Both processes require an active actin cytoskeleton. The cell movement induced by the hydrodynamic forces is very similar to amoeboid cell motion during chemotaxis, as for its kinematic parameters and for the involvement of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 49 publications
(40 reference statements)
4
71
0
Order By: Relevance
“…Similarly to chemotaxing cells, several studies have reported activation and/or localization of typical leading edge markers, including actin polymerization, phosphatidylinositol 3,4,5-trisphosphate (PIP3), and/or extracellular signal-regulated kinase (ERK) 1/2, at the front of cells undergoing either shear-flowmediated migration or electrotaxis (4)(5)(6)(7). However, these activities were observed under steady-state conditions and, because these activities are associated with random projections, their appearance at the leading edge most likely merely reflects the abundance of projections at the front induced by mechanical or electrical forces.…”
mentioning
confidence: 99%
“…Similarly to chemotaxing cells, several studies have reported activation and/or localization of typical leading edge markers, including actin polymerization, phosphatidylinositol 3,4,5-trisphosphate (PIP3), and/or extracellular signal-regulated kinase (ERK) 1/2, at the front of cells undergoing either shear-flowmediated migration or electrotaxis (4)(5)(6)(7). However, these activities were observed under steady-state conditions and, because these activities are associated with random projections, their appearance at the leading edge most likely merely reflects the abundance of projections at the front induced by mechanical or electrical forces.…”
mentioning
confidence: 99%
“…We also observed the behavior of phg2 cells in conditions where motility is stimulated by a controlled flow of medium ( Figure 9D) (Decave et al, 2003). This flow is not sufficient to detach the cells, but induces a marked increase in cell motility ( Figure 9E).…”
Section: Phg2 Is Required For Cell Motility and Mechanotransductionmentioning
confidence: 82%
“…Shear-stress induced motility was determined in a lateral flow chamber according to Decave et al (2003). Briefly, cells were introduced in the flow chamber and adhered during 2 min.…”
Section: Cellular Adhesion and Motilitymentioning
confidence: 99%
“…NS, not significant. NATURE COMMUNICATIONS | DOI: 10.1038/ncomms6213 ARTICLE of Dictyostelium discoideum 23 , Entamoeba histolytica 24 and endothelial cells 25 . However, inhibitors of phosphoinositide 3-kinases or G-protein-coupled receptors (Supplementary Note 5 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological benefit of flow orientation is currently unknown for lymphocytes and more generally for neutrophils 16 , endothelial cells 9 or amoebae 23 . The fact that neutrophils crawl downstream 16 and T lymphocytes upstream 4 while migrating on the same adhesive ligand, challenges the idea of a universal flowguided mechanism selected to favour extravasation.…”
Section: Discussionmentioning
confidence: 99%